Effectiveness of Parenting styles on Psychosocial among Adolescents: A Systematic Literature Review - Indrianti, Adelia; Fitriani, Azma Nur; Septiani, Hani; Putri, Rania Herdiani; Fauziah, Diny Nur; Lismayanti, Lilis (Inspirasi Foundation, 2026)
Introduction: Parenting styles play a crucial role in adolescents’ psychosocial development, including emotional health, social relationships, and cognitive growth. The manner in which parents nurture their children can influence adolescents’ levels of anxiety and depression. Parenting that is authoritative tends to promote better mental health, while an authoritarian style is commonly related to an increased risk of psychological problems. Objective: This systematic review seeks to investigate the impact of various parenting styles authoritative, authoritarian, permissive, and neglectful on the psychosocial well-being of adolescents. Method: The literature review included studies published from January 1, 2012, to December 31, 2024, which were sourced from four different databases: PubMed, ProQuest, JSTOR, and Garuda. The target population was adolescents aged 11 to 19 years. Parenting styles were evaluated using the Parental Authority Questionnaire (PAQ), while mental health outcomes were assessed through various instruments, This included measures such as the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), General Health Questionnaire-28 (GHQ-28), Multidimensional Psychological Flexibility Inventory (MPFI), Hamilton Depression Rating Scale (HAM-D), and the Massachusetts Youth Screening Instrument, Version 2 (MAYSI-2), and the Mental Health Continuum-Short Form (MHC-SF). Three reviewers independently carried out article screening, data extraction, and quality assessment, following the PRISMA framework. Study quality was further appraised using the CASP checklist. The extracted information included author details, type of intervention, facilitator, research setting, number and length of sessions, as well as the methods or media employed. Result: A total of nine articles involving 2,036 participants were included. The results indicate that parenting styles have a notable influence on adolescents’ psychosocial well-being. Adolescents with authoritative parents showed higher psychological flexibility, whereas those with authoritarian parents experienced increased anxiety, depression, and socio-emotional challenges. Conclusion: The review concludes that authoritative parenting is the most effective approach for promoting adolescents’ psychosocial well-being. It enhances self-esteem and psychological flexibility while lowering anxiety and depression. Parenting education and targeted interventions should therefore be encouraged in clinical practice to foster authoritative parenting and promote adolescents’ mental well-being.